Knowledge mapping of immune thrombocytopenia: a bibliometric study - Wu, Feifeng; Li, Cuifang; Mao, Jueyi; Zhu, Junquan; Wang, Yang; Wen, Chuan (Frontiers in Immunology, 2023)
Background: Immune thrombocytopenia (ITP) is an autoimmune disease characterized by isolated thrombocytopenia. Recently, the pathophysiology and novel drugs of ITP have been the focus of researchers with plenty of publications emerging. Bibliometrics is the process of extracting measurable data through statistical analysis of published research studies to provide insight into the trends and hotspots. Objective: This study aims to provide insights into developing trends and hotspots in the field of ITP by scientometric analysis. Methods: By using three bibliometric mapping tools (bibliometrix R package, VOSviewer, CiteSpace), we summarized the overview information of retrieved publications, as well as the analysis of keywords co-occurrences and references co-citation. Results: The search in the WoS database resulted in a total of 3,402 publications with 8781 citations on ITP research. Then the most impact authors, countries, regions, and sources were identified in this field. The keyword co-occurrence network identified 4 clusters relating to the diagnosis, pathophysiology, and treatment of ITP respectively. Then the reference co-citation analysis produced 12 clusters with a well-structured and highly credible clustering model, and they can be divided into 5 trends: second-line treatment, chronic ITP, novel therapy and pathogenesis, COVID-19 vaccine. Mesenchymal stem cells, spleen tyrosine kinase, t cell subsets were the latest hotspots with strong burstness. Conclusion: This bibliometric analysis first provided a comprehensive insight into research hotspots and trends on ITP, which would enrich the review of the ITP research and help researchers grasp the points.